PENINGKATAN MINAT DAN HASIL BELAJAR KETERAMPILAN BERBICARA MENGGUNAKAN METODE MIND MAP PADA MAHASISWA KELAS IA PBSI IKIP PGRI BOJONEGORO TAHUN AKADEMIK 2019/2020 - Agus Darmuki; Ahmad Hariyadi; Nur Alfin Hidayati (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2020)
This research aims to increase the interest and learning outcomes of speaking skills in IA class students of PBSI IKIP IKRI PGRI Bojonegoro Academic Year 2019/2020. This class action research uses 2 cycles, each cycle consisting of planning, implementation, observation, and reflection. This research was conducted in the IA class of PBSI IKIP IKIP PGRI Bojonegoro Academic Year 2019/2020 odd semester with a total of 30 students with details of 8 male and 22 female, aged between 17-24 years. The data collection techniques of this study used questionnaires, observations, interviews and documentation. The results of the questionnaire in cycle 1 amounted to 60%, an increase in interest in learning to speak increased in cycle 2, namely 96.7%. Student learning outcomes average pre-cycle knowledge value of 65.4, cycle 1 an average value of 72, 7, and cycle 2 77.0. While the average value of the skills value is 69.0 in the pre-cycle stage, 76.2 in cycle 1 and 78.0 in cycle 2. The conclusion of this study mind map method applied can increase the interest and learning outcomes of speaking skills in IA class students PBSI IKIP PGRI Bojonegoro Study Program Academic Year 2019/2020.